Evaluation of ber (Ziziphus mauritiana) genotypes under semi-arid region of Haryana - KUMAR, SANJAY; SHARMA, JEET RAM; KUMAR, MUKESH; BISHNOI, MUKESH; REETIKA; GAVRI, ANKIT (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2020–21 and 2022–23 at Regional Research Station (CCS Haryana Agricultural University, Hisar, Haryana), Bawal, Haryana for characterizing 35 distinct ber (Ziziphus mauritiana Lamk.) genotypes by evaluating their 16 morphological attributes as growth habits, foliage and thorn characteristics. The experiment was laid out in randomized block design (RBD) with three replications. Among selected genotypes, an upright growth pattern was reported in five genotypes, whereas, the most of the genotypes displayed a semi-erect growth habit. All the genotypes showed tomentose shoot surface. Further, four distinct leaf shapes were documented. Ovate leaf shape was exhibited by 15 genotypes, while 8 genotypes displayed oval and 6 genotypes showed cordate and obovate type leaf each. The maximum leaf blade length (10.63 cm) and width (7.31 cm) was recorded in Thar Sevika, while, the minimum size of leaf blade length was noticed in Sanori (6.95 cm) and width was found in Katha Bombay (3.86 cm). In response to branch thorniness, the less branch thorniness was found in Illaichi, Naki, Umran and Kaithali, while two genotypes revealed high branch thorniness (Tasbtso, Narkali). Only two types of thorn shape were noticed, as out of 35 genotypes, 21 had alternate curved thorn. Based on anthocyanin blush of immature fruit, genotypes Kathaphal, Sanori and Narkali had reddish blush on fruit. Further, theses genotypes were categorized into early, mid and late on the basis of fruit maturity. Six genotypes showed early maturing fruits, while 21 genotypes were mid-season and 8 were late maturing genotypes. The bunch bearing of fruit was noticed only in two genotypes (Jhajjar Selection and BS 2). It is worth highlighting that all these genotypes under study exhibited substantial variability across various morphological traits, which can potentially be attributed to genetic disparities stemming from the diverse ancestral species from which these cultivated genotypes originated.